Pengaruh Profitabilitas terhadap Return Saham pada Sub Sektor Konstruksi Bangunan yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2020 - April Nadia Putri (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of simultan and partial variable Return On Asset, Return On Equity, Net Profit Margin, and Gross Profit Margin.This research uses descriptive quantitative method and the source of the data in thid study was obtained through several literatures related to research, the website of the company concerned, financial statements and the Indonesia Stock Exchange (IDX).The object of this research is a Building Construction Company which is one of the Sub-Sector categories on the Indonesian stock exchange with a research population of 18 companies, only 6 companies are the research samples according to the sampling criteria.The examiner shows that simultaneously Return On asset,Return On Equity,Net Profit Margin and Gross Profit Margin have a significant effect on stock Return.With a significant value of 0,026, the Return On Asset test partially has a positive effect with a significant value of 0,022 on stock Return. Return On Equity has no positive effect with a significant value of 0,086 on stock Return. Net Profit Margin has a positive effect with a significant value of 0,031 on stock Return. Gross Profit Margin has no positive effect with a significant value of 0,512 0n stock return. The results of this study indicate that simultaneously the Return On Asset, Return On Equity, Net Profit Margin and Gross Profit Margin variables have a significant effect on stock Returns. Partially, return on Asset and Net Profit Margin have a significant effeck, while Return On Equity and Gross Profit Margin have no significant effect. For further writers, it is better to use more variables to see effect of variables on stock Returns, so that investors can be taken into consideration in making decisions.